Traumatic wound difficult to heal: use of negative pressure therapy: case report - Salas Ochoa, Edgar Salvador; Arce Sanchez, Edilia Naraleth; Altamirano Moreno, Karla Itzel; Segura Garcia, Edna Arantza; Peña Sustaita, Leslie Alejandra; Mecado Flores, Gissel Alejandra (International Journal of Research in Medical Sciences, 2021)
The skin is one of the largest organs of the anatomy. It is the barrier between the exterior and the first line of defense against aggression. A wound is a loss of continuity of the soft parts of the organism generating an interruption in the structure of the tissue, as a consequence of this loss of continuity, there is a loss of sterility existing inside and infection can occur. Another consequence of discontinuity are possible lesions in adjacent tissues or organs. Trauma results in complex wounds that are difficult to manage due to large skin loss or avulsion of large areas of tissue. Among the factors that can prevent proper healing can be systemic (malnutrition, chemotherapy, steroids) or local (infection, prosthetic material, bone exposure). Among the therapeutic options for complex wounds is negative pressure therapy which generates wound contraction, stabilization of the environment, reduction of edema, removal of exudate and micro-deformations of the surface, increase of angiogenesis, granulation tissue formation and decreased bacterial count. We described a clinical case of traumatic injury at the level of the right pelvic limb in a 70-years-old woman with diabetes and hypertension, in which surgical washing was performed, debridement and use of negative pressure therapy with adequate evolution in a second level public hospital.